Helicobacter pylori & beyond: pediatric peptic ulcer disease. Issue 1 (January 2009) - Shashidhar, Harohalli; Flomenhoft, Deborah; Tolia, Vasundhara
The word peptic implies ''gastric-, pepsin- or acid-related''. Peptic ulcer disease (PUD) denotes the presence of gastric and/or duodenal ulceration or erosion. In clinical practice, the term encompasses gastric or duodenal inflammation due to any etiology, and may be more common in childhood than ulcerative disease. PUD occurs across the pediatric age group. Although etiopathology of PUD is typically related to that of Helicobacter pylori infection, other etiology for PUD is not uncommon in children and requires a different approach in evaluation and therapeutic decisions. Evaluation of PUD includes endoscopy with mucosal biopsy. Noninvasive testing, such as urea breath test, has a role in the follow-up of H. pylori eradication following therapy. Better understanding of pathogenic factors innate to H. pylori infection has enhanced our understanding of associated PUD. This review describes the management of both H. pylori and non- H. pylori PUD.